Inadequacy of the ECB’s monetary policy in the EU economies outside the eurozone - Klus, Sylwia; Paluszak, Grzegorz; Urbanowicz, Zuzanna (Nieadekwatność polityki pieniężnej EBC w unijnych gospodarkach spoza strefy euro, 2019)
The aim of the article is to estimate the extent of the inadequacy of the European Central Bank’s (ECB’s) monetary policy to the economies of those EU member states which have not joined the euro area so far. The assessment of the extent of maladjustment of the single monetary policy is based upon a counterfactual analysis and is carried out for the economies with the so-called derogation from the Economic and Monetary Union (EMU) since the ECB started to operate. The status of a derogation means that a member state is formally obliged to adopt the single currency euro and must face the consequences resulting from the single monetary policy in the context of economic macro-stabilization. The results obtained may be useful in a discussion on the moment of accession to the eurozone
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 9, s. 58-67
Keywords: inadequacy; ECB; monetary policy; eurozone; European Union economies; nieadekwatność; EBC; polityka pieniężna; strefa euro; gospodarki europejskie